Temperature and Coefficient of Performance Test for Cooling Machine - Wahyu Aditya Sp; AS Mukti; RF Aditama; RMZH Putra; WAS Putra; RR Hidayat; MN Ardhany; MW Rosyadi; RDK Mahameru (BIOMEJ, 2024)
A cooling machine is a mechanism in the form of a cycle that takes energy (thermal) from a low temperature area and discharges it to a high temperature area (environment), so that the cooling load greatly influences the performance of the cooling machine. The greater the cooling load being cooled, the greater the cooling engine power will be required. Likewise, the smaller the cooling load, the smaller the cooling engine power required. The method used in this experiment is a quantitative method where we collect data and then process the data to get the Coefficient of Performance (COP) value. Based on the observations from the data collection results, it was found that in the 5th minute to the 30th minute there was a decrease in temperature, where the room temperature in the cooling machine was initially 24°C and the temperature decrease began to occur in the measurement at the 5th minute, amounting to 20.5° C, at the 10th minute it was 20.42°C, at the 15th minute it was 19.04°C, at the 20th minute it was 18.06°C, at the 25th minute it was 17.94°C, and at the 30th minute it was 17.82°C. From the actual COP data, in minutes 5 to 10 there was a decrease in temperature of 0.46%, where this percentage shows that there has not been a significant decrease in temperature, where a fairly high decrease occurred in the 15th to 20 minutes, where the percentages are consecutive. -also shows 7.95% and 5.64%. From the 25th to the 30th minute, the rate of decline began to remain constant again with a percentage of only 0.69%.